STRATEGIES TO INCREASE THE MOTIVATION OF THE INDONESIAN ISLAMIC STUDENT REGIONAL MANAGEMENT ORGANIZATION IN SOUTH SUMATRA - Asriani, Puji; Achmad Syarifudin; Muhammad Randicha Hamandia (CV. Doki Course and Training, 2023)
This research is entitled Strategies to Increase Organizational Motivation of Indonesian Islamic Student Area Management in South Sumatra (Study of Organizational Communication Patterns). The purpose of the research in this case the communication pattern used is all channels, namely the head of the leadership, and all cadre administrators to be able to interact and provide the desired information and also with the interaction of fellow administrators of the Indonesian Islamic Student organization (PII). The method used in this study the author used a qualitative approach. The data sources used in this study are primary data sources and secondary data. The data collection method used in this study was the interview and observation method in the field. The results of this study show that the strategy of the communication pattern of the organization of the Indonesian Islamic student area management in increasing organizational motivation is very good and very important to increase motivation in organizing because by using good communication the message will be conveyed well to the communicants and will get good feedback, in increasing motivation in organizing of course we must feel comfortable with the surrounding environment thus giving rise to a sense of openness to each other. This aims to create a sense of mutual respect, tolerance between fellow board members, and also create a sense of enthusiasm to exchange information with each other with the aim of increasing the insight and knowledge gained, completing all tasks in their respective fields.